Approaches to Shaping the Financial Strategy of Zombie Businesses - Kirill Kurilov; Anastasia Kurilova (Communications of International Proceedings, 2020)
The debt market is currently characterized by the growth of bad debts of the corporate sector and states. A particularly alarming trend is in the corporate sector, which is seeing a rise in the number of zombie businesses, which are businesses that cannot pay off payables and only pay interest payments on them. The negative point is that these enterprises issue financial assets, including bonds that are bought by well-known and large companies such as Apple, Facebook, Google, etc. Thus, toxic assets are spreading throughout the economy, spreading the risks of insolvent economic actors throughout aggregate. In the context of the growing risks of massive non-payments, the relevance of the formation and use of the financial strategy of the enterprise, adapted for zombie enterprises, increases.
Keywords: Zombie businesses; financial strategy; junk bonds; financial investments.